Ageing durability of SiR under prolonged voltage stress, contaminant flow and contaminant concentration: a statistical approach - Nazir Ali, Nornazurah; Zainuddin, Hidayat; Abd Razak, Jeefferie; Farhani Ambo, Nur (Bulletin of Electrical Engineering and Informatics, 2024)
Silicone rubber (SiR) has become a reliable choice for outdoor high voltage (HV) insulation in recent years. However, the durability of these polymeric materials is affected by both electrical and environmental stresses, leading to aging. While prior research aimed at enhancing performance, little focus was placed on identifying the major root causes of aging in these insulators. To delve into the causes, we conducted inclined plane tracking (IPT) tests, varying voltage, flow rate, and contamination concentration. Samples with consistent alumina trihydrate (ATH) filler content were tested under the BSEN 60587 standard. The voltage ranged from 3.5-5.5 kV, flow rate from 0.3-0.9 ml/min, and contamination concentration from 500-4500 µS/cm. A Two-Level Factorial analysis with a design of experiment (DOE) approach was used. The study revealed that contaminant concentration significantly impacted leakage current (LC), followed by contamination flow rate and voltage. Additionally, optimization techniques are used to determine ideal LC values under specific conditions. This study explains how each factor affects LC values, allowing for predictive modelling, which improves our understanding of SiR insulators' durability, optimizes LC in real-world situations, and improves their performance and lifespan.